Impact of Bio-fertilizers under Supplementary Irrigation and Rain-fed Conditions on Some Physiological Responses and Forage Quality of Smooth Vetch (Vicia dasycarpa L.) - Rashid Jamei; Alireza Pirzad; Saeid Heydarzadeh; Jalal Jalilian (Journal of Agricultural Sciences)
The purpose of this study was the evaluate use of bio-fertilizers to adjustment water shortage stress and improved smooth vetch (Vicia dasycarpa L.) yield under water deficit stress conditions. Thus, A 2-year experiment were performed in an agrisilviculture system of plum orchard in 2016 and 2017. In this study, the single, double and triple combined of Arbuscular mycorrhizal fungi- Rhizophagus intraradices (AMF), Azotobacter chroococcum (Az) and Thiobacillus spp. (Th) on smooth vetch plants were evaluated under rain-fed and supplemental irrigation. The results indicated that irrigated plants had more Fe and Zn nutrients than rain-fed plants. Combined use of AMF + A. chroococcum more improved the forage dry matter digestibility (DMD), total digestible nutrient (TDN), net energy for lactation (NEL), dry matter intake (DMI) and relative feed value (RFV) than plants with single inoculation. In irrigated plants, double and triple combination of AMF with A. chroococcum and/or Thiobacillus spp. improved chlorophyll-a, chlorophyll-b, total chlorophyll, RWC, TSS, AsA, and GSH while lowering proline and MDA. Rain-fed condition reduced grain yield. In conclusion, synthesis non-enzymatic antioxidant because of the combined use of bio-fertilizers (AMF, Az and Th) can reduce ROS damage and improve water deficit resistance and yield in smooth vetch rain-fed plants.